Tick-borne encephalitis: What travelers should know when visiting an endemic country - Chrdle, Aleš; Chmelík, Václav; Růžek, Daniel (Human vaccines & immunotherapeutics, 2016)
Tick-borne encephalitis (TBE) is an acute febrile illness with neurological manifestations that is prevalent in forested areas of moderate climate in Europe and Asia. TBE virus is transmitted by ticks and rarely by unpasteurized milk and dairy products. The disease burden is attributed mainly to resulting long-term disability, especially in individuals over 50 y of age. Currently, there is no causative treatment, but a very effective vaccination is available with a good safety profile. The vaccination requires 3 basic doses to be fully effective and regular boosters afterwards. An accelerated vaccination schedule enables a patient to reach reasonably protective titres within 3 to 4 weeks from the first injection. The risk of travel-related TBE is estimated to be less than the risk of acquiring typhoid fever while visiting highly endemic regions in South Asia, but more than the risk of acquiring Japanese encephalitis, meningococcal invasive disease, or rabies. The pre-travel risk assessment of acquiring TBE should consider known risk factors which include 1) the country and regions to be visited; 2) April to November season; 3) altitude less than 1500 m above the sea level; 4) duration of stay; 5) the extent of tick-exposure associated activities including leisure and professional outdoor activities within the endemic area; and 6) age and comorbidities of the traveler. A major challenge, however, is the very low awareness of the risk of contracting TBE in those who travel to industrialized European countries.
Keywords: Humans; Encephalitis, Tick-Borne; klíšťová encefalitida; Evropa; Viral Vaccines; Asie; tick-borne encephalitis; lidé; cestování; Europe; endemické nemoci; endemic country; tick-borne encephalitis virus; virové vakcíny; Endemic Diseases; Asia; flavivirus; vaccination; travel medicine; Travel